ASSESSMENT AND FACTORS OF RISK IN AN IPO’S - Shukla, Jyoti (International Journal of Engineering Technologies and Management Research, 2017)
In present scenario IPO’s are the best way of investment for the good returns as well. These IPO’s totally depends on market. Investment in IPO’s may contain risk factor and may be harmful in terms of loss. So, in this paper the risk assessment and risk factors associated with IPO’s should be described so that one can get to know about theses risk and their impact on IPO’s. This paper will also help researcher for their study related IPO and their associated risk. In this paper author described introduction to IPO and what kind of risk can be there investing in IPO.